Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Berdasarkan Prestasi Kerja Pada PDAM Surya Sembada Kota Surabaya - Syamsiah, Shirly; Amelia, Tan; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
PDAM Surya Sembada is a local company that is responsible for providing clean water in the city of Surabaya. As a local company that is responsible for serving the community, then PDAM Surya Sembada seeks to monitor the development of enterprise organizations that are useful to improve the quality of the company.To see the development of an organization is to assess the performance of Human Resources (HR), its called the assessment of performance based employee performance. Performance appraisal results can indicate whether HR (employees) on stretcher organization has met the objectives / targets as requested by the organization, both in quantity and quality, how the behavior of employees in carrying out their work, how the use of working time and so on.The benefits obtained by the application of employee performance evaluation based on job performance, among other things: work units can take into account the results of the work program achievement compared with the results achieved, the expected performance of employees will be more measurable, their feedback to improve performance, and the monitoring and evaluation of leadership in order to improve employee performance.